Coaching Belgian and Dutch Broiler Farmers Aimed at Antimicrobial Stewardship and Disease Prevention - Nele Caekebeke; Moniek Ringenier; Franca J. Jonquiere; Tijs J. Tobias; Merel Postma; Angelique van den Hoogen; Manon A. M. Houben; Francisca C. Velkers; Nathalie Sleeckx; Arjan Stegeman; Jeroen Dewulf; on behalf of the i- 4-1-Health Study Group (MDPI AG, 2021)
A reduction in antimicrobial use (AMU) is needed to curb the increase in antimicrobial resistance in broiler production. Improvements in biosecurity can contribute to a lower incidence of disease and thereby lower the need for AMU. However, veterinary advice related to AMU reduction or biosecurity is often not complied with, and this has been linked to the attitudes of farmers. Behavior change promoted by coaching may facilitate uptake and compliance regarding veterinary advice. Thirty broiler farms in Belgium and the Netherlands with high AMU were included in this study for 13 months. For each farmer, the attitude towards AMU reduction was quantified using an adjusted Awareness, Desire, Knowledge, Ability, and Reinforcement (ADKAR®) change management model, and farm biosecurity was assessed with the Biocheck.UGent™ tool. Subsequently, farmers were coached to improve disease prevention and antimicrobial stewardship. After the individual coaching of farmers, there was a change in their attitudes regarding AMU, reflected by an increase in ADKAR® scores. Biosecurity levels improved by around 6% on average, and AMU was reduced by 7% on average without negative effects on performance parameters. Despite these improvements, no significant association could be found between higher ADKAR® scores and lower AMU. Further investigation into sociological models is needed as a tool to reduce AMU in livestock production.